Histological analysis of effects of 24% EDTA gel for nonsurgical treatment of periodontal tissues - Vasconcellos, Luana Marotta Reis de [UNESP]; Ricardo, Lucilene Hernandes; Balducci, Ivan [UNESP]; Vasconcellos, Luis Gustavo Oliveira de; Carvalho, Yasmin Rodarte [UNESP] (Nihon University School of Dentistry, 2006)
The aim of this study was to investigate, by means of histological and histomorphometric analysis, the effects of 24% ethylenediaminetetraacetic acid (EDTA) gel in periodontal tissue when used in combination with conventional periodontal treatment. Periodontitis was induced in the 2nd upper left permanent molars of 45 male Wistar rats by means of ligature. After 5 weeks, this was removed and debridement was performed. The animals were then randomly divided into 3 groups; group 1: mechanical treatment, group 2: mechanical treatment and EDTA gel application for 2 min, and group 3: mechanical treatment and placebo gel application for 2 min. After the treatment, rinsing was done with 0.9% saline solution for 1 min in all cases, followed by root notching in the deepest part of the pocket. After 4, 10, and 28 days the animals were sacrificed. The averages obtained were evaluated by means of test two-way analysis of variance (ANOVA) and Tukey statistical tests (P < 0.05). The results showed that with respect to the type of treatment employed, there were no statistically significant differences in the vitality of the periodontal tissue. It was concluded that 24% EDTA gel did not interfere with periodontal tissue repair when used in combination with conventional periodontal treatment.